Fiscal policy: Coordination, discipline and stabilisation - Anne Brunila (Bank of Finland, 2002)
The framework for fiscal policy coordination in EMU has been in effect for three years.The experience gained shows that the rule-based approach provides in principle a feasible solution for policy coordination among a large number of heterogeneous countries whose joint interest is to safeguard the credibility of the common monetary policy and smooth functioning of the EMU.At the same time, the experience indicates that the current set of rules and procedures laid down in the Maastricht Treaty and Stability and Growth Pact (SGP) suffer from complexity, lack of transparency and asymmetric incentives.The paper discusses the rationale for fiscal policy coordination in the monetary union in general and emphasises the role of fiscal rules and multilateral surveillance in ensuring discipline and long-term sustainability of public finances.The paper also considers incentive problems arising from the asymmetric nature of the SGP and weak interaction between national policy-making and EU-level policy commitments.As a possible remedy, the paper proposes complementing the SGP with medium-term expenditure rules for central governments and balanced budget requirements for lower levels of government.
URN:NBN:fi:bof-20140807315
Keywords: 330; fiscal policy coordination; expenditure rules; Stability and Growth Pact